2022
DOI: 10.1007/s10484-022-09574-y
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Heartbeat Tracking Task to Assess Interoception

Abstract: Interoception refers to the competence in perceiving and interpreting internal sensations emerging from the body. The most common approach to assess interoception is through cardiac interoceptive tests like the heartbeat tracking task (HTT), which measures the accuracy on perceive and counting heartbeats during a period. However, the literature is scarce in providing adequate reliability evidence for this measure so that the interoception assessment may be threaten. In addition to HTT accuracy, it is possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Nevertheless, according to other research, the results of HCT correspond well with other interoceptive tasks ( 79 ). Recently, a study indicated that HCT can be a reliable test in assessing interoceptive accuracy ( 80 ). In the absence of alternative methods to study this phenomenon, we decided to use HCT, which will further allow us to compare our results with those obtained in prior work.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, according to other research, the results of HCT correspond well with other interoceptive tasks ( 79 ). Recently, a study indicated that HCT can be a reliable test in assessing interoceptive accuracy ( 80 ). In the absence of alternative methods to study this phenomenon, we decided to use HCT, which will further allow us to compare our results with those obtained in prior work.…”
Section: Discussionmentioning
confidence: 99%